The Future of Carbon Market and its impact on Business (International Journal of Scientific Research and Management (IJSRM), 2015)
The Carbon market is now the one of the fastest market in India. The companies that are not already carbon constrained will need to prepare themselves for carbon legislation as a low carbon economy in the long run. This research is used for the future of carbon market and its impact on business. Some companies are already taken lots of monetary and non-monetary benefits but nowadays several organizations are directly interested to involve in this trading. This concept is basically generated from the Kyoto Protocol. The main aim of this protocol is to reduce the carbon emission. This concept is mainly coined and operated on the basis of Clean Development Mechanism (CDM), which is used to earn carbon credit earnings and carbon trading between the various companies and the central government. The Kyoto Protocol mechanism is basically the only internationally agreed mechanism for regulating the carbon credit activities and includes checks for additionality and overall effectiveness. It’s supporting organization, the Union Nations Framework Convention on Climate Change Ajay K. Garg, IJSRM volume 3 issue 1 January, 2015 [www.ijsrm.in] Page 2035 (UNFCC), is the only organization with a global mandate on the overall effectiveness of emission control systems. A global carbon market could be a system where all major emitters and industrialized countries are carbon constrained domestically and developing countries provide offsets on a large scale through efficient market mechanisms. So, this research is basically used to show the future of carbon credit trading in the developing countries and its impact on the business of various organizations.